Fruitcake [compact disc] - Carpenter, Sabrina (Island, 2024)
The six-track debut holiday EP from Sabrina Carpenter is a collection of five original songs alongside fan-favorite and previously released "A Nonsense Christmas," a festive lyrical twist on her first Top 40 Radio #1 hit, "Nonsense." Just sayin,' we've never seen Santa Claus and Sabrina Carpenter in the same room.